Vadr går gränsen? (Sociologisk Forskning, 2006)
This article introduces a study concerning parents regulations regarding their child’s participation in social activities. The aim of the study is to examine how many pupils who are not allowed to participate in social activities and some educational elements at school, as for example sports and study tours. The ethnicity and gender perspectives are central for the questions. The implicit aim is to compare the situation among boys and girls with immigrant background in relation to boys and girls with Swedish background. The study contains a quantitative survey among 1193 children, 13 to 15 years old, living in a Swedish middle-sized city. The result from the analysis shows that most of the children are allowed to participate in the activities. However, regarding parental consent to participating in activities the results show that children with immigrant background experience restrictions to a larger extent than others. This result concerns in particular girls with immigrant background. Other significant findings in this study indicate that low-educated parents or/and religious parents have more restrictive norms considering pupils participating in social activities, especially for immigrant girls.
Keywords: School; education; immigrant; gender; children